Potential of CuS cap to prevent decomposition of Cu2ZnSnS4 during annealing. Issue 12 (26th August 2015) - Larsen, Jes K.; Scragg, Jonathan J. S.; Frisk, Christopher; Ren, Yi; Platzer‐Björkman, Charlotte
Abstract : One of the challenges associated with processing of Cu2 ZnSnS4 (CZTS) is the thermal decomposition reaction that causes loss of S and SnS from the absorber surface. To reduce the decomposition a sufficiently high SnS and S partial pressure must be supplied during annealing. The absorber surface can alternatively be protected with a thin cap. Aiming to obtain a more flexible process, CZTS precursors were capped with a thin CuS layer before annealing. The cap was subsequently removed with a KCN etch before device finishing. It was found that the cap coverage decreased during annealing, exposing a part of the absorber surface. At the same time, the initially Cu poor absorber took up Cu from the cap, ending up with a stoichiometric Cu content. Devices made from capped precursors or precursors annealed without sulfur had poor device characteristics. An increased doping density of almost one order of magnitude could be the reason for the very poor performance. CuS is therefore not a suitable cap material for CZTS. Other cap materials could be investigated to protect the CZTS absorber surface during annealing. A thin CuS cap is deposited on CZTS to prevent surface decomposition during annealing.